Pendampingan Penyusunan Konten Edukasi Digital Keterlibatan Pemuda Pulau Terluar Enggano Untuk Meningkatkan Kesadaran Dalan Mempromosikan Budaya, Wisata, Dan Produk Umkm Lokal - Sri Ihsan; Safna Kurnia Putri; Ikhsan Fernando (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2026)
The rapid advancement of digital technology has created significant opportunities to promote local culture, tourism destinations, and Micro, Small, and Medium Enterprises (MSMEs) in remote areas, including Enggano Island, Bengkulu Province, Indonesia. Despite this potential, the community continues to face several challenges, such as limited digital literacy, inadequate skills in digital content creation, and minimal participation of young people in utilizing digital platforms to support local development. These constraints have hindered the effective promotion of the island’s cultural heritage, tourism attractions, and local products to broader audiences. This community service program aimed to enhance the digital competencies of local youth through training and mentoring in the development of educational and promotional digital content. The program adopted the Participatory Action Research (PAR) approach, emphasizing active community participation throughout the stages of needs assessment, planning, implementation, reflection, and evaluation. Various activities were conducted, including workshops on digital literacy, social media management, visual content creation, and strategies for promoting local tourism and MSME products. The findings indicate a substantial improvement in participants’ knowledge, technical skills, and confidence in creating and disseminating digital content through social media platforms. Furthermore, the program increased participants’ awareness of the productive and responsible use of digital technology while fostering collaboration among youth in preserving local culture and supporting community-based economic development. Overall, this initiative demonstrates that participatory digital literacy programs can strengthen local cultural identity, expand the visibility of tourism and MSME products, and contribute to sustainable socio-economic development in rural and island communities.